(untitled) (Innovate Conferences, 2025)
Zoonymic expressions—words and phrases that derive from or involve the names of animals (zoonyms)—play a significant role in human language, functioning both lexically and stylistically. This paper explores the vocabulary of zoonymic expressions and their stylistic features, focusing on their metaphorical usage, cultural symbolism, and communicative functions in both everyday and literary discourse. The study also examines the cognitive and linguistic mechanisms behind the use of zoonyms in idiomatic expressions, proverbs, and slang, offering insight into the anthropocentric worldview reflected in language.